The Psychological Consequences of the False Self in Jean Kwok’s Searching for Sylvie Lee - Nabila Lathifa Az Zahra Zahra; Prayudias Margawati (Universitas Cokroaminoto Palopo, 2026)
Family should be the safest place for everyone, where people can become their true selves and express their true feelings. On the contrary, the main character in Searching for Sylvie Lee often shows the dominance of her false self and hides her true self from her family. Therefore, this study explores how the character’s childhood environment contributes to the formation of her false self and its effect on her authentic self-expression and psychological stability. Through a qualitative descriptive method within a psychoanalytic literary criticism framework, the study analyzes narrative descriptions, dialogues, character interactions, and internal reflections in the novel using Winnicott’s concepts of the holding environment, true self, and false self. The findings reveal that the character’s prolonged separation from her biological parents, emotional rejection, conditional acceptance, and persistent feelings of displacement contribute significantly to the formation of her false self. As she grows older, this adaptive identity becomes increasingly dominant, shaping her into the person everyone needed, until nobody knows who she really is. This prolonged dominance of the false self results in loneliness, emotional isolation, difficulties in expressing vulnerability, loss of authentic selfhood, and psychological collapse. The discussion suggests that the character’s tragedy is rooted not only in external circumstances, such as migration and family conflict, but also in the ongoing suppression of her authentic self to maintain social acceptance.